Toxicology of Processed and Packaged Foods - Srivatsa, A. N.; Sharma, T. R. (Defence Science Journal, 2014)
Modem food production, processing and preservation use a large number of additives at various stages. These include food sweetners, preservatives, colours, antioxidants and pesticides. In addition, the foods come in contact with packaging materials which by themselves contain a large number of additives. Some of these are potential sources of hazards to consumers. This paper is a review of investigations which have been carried out on some of the additives, the migration of additives from packing systems and naturally occurring toxic substances as possible health hazards.